Critical thinking efficacy and transfer skills defend against 'fake news' at an international school in Finland - Horn S.; Veermans K. (SAGE PUBLICATIONS LTD, 2022)
In this study, tasks measuring digital media literacy developed by Stanford University were administered at a school in Finland to consider the efficacy and transfer of critical thinking (CT) skills of a 'pre-IB' cohort preparing to enter the two year International Baccalaureate Diploma Programme (IBDP) and a graduating 'IB2' cohort. While the IB2 cohort outperformed the pre-IB cohort, both outperformed Stanford's U.S. cohorts to a statistically significant degree. Utilising a framework of curricular approaches to facilitating CT skills development as a variable of interest for causal-comparison, it was determined that the Finnish curricula and the IBDP explicitly facilitate CT skills as a separate course while embedding CT into subject coursework, whereas the curriculum in the U.S. implicitly embeds CT into subject coursework only. Implications for improving facilitation of CT in curricula design, professionalising CT across the field, and the benefits of replicating existing studies in differing socio-educational environments are discussed.